2019
DOI: 10.1016/j.ijmultiphaseflow.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of viscous fluid flow in a pressure-swirl atomizer using large-eddy simulation

Abstract: A computational fluid dynamics study is carried out on the inner nozzle flow and onset of liquid sheet instability in a large-scale pressure-swirl atomizer with asymmetric inflow configuration for high viscosity fluids. Large-eddy simulations (LES) of the two-phase flow indicate the unsteady flow character inside the nozzle and its influence on liquid sheet formation. A novel geometric volume-offluid (VOF) method by Roenby et al., termed isoAdvector, is applied for sharp interface capturing (Roenby J., Bredmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The correlation predicted the film thickness with high accuracy up to pressures of 3 MPa. Other recent studies with different atomizer geometries, pressures, and liquid properties have found that the expression estimates the liquid film thickness fairly well (Laurila et al, 2019;Wimmer & Brenn, 2013).…”
Section: Introductionmentioning
confidence: 69%
“…The correlation predicted the film thickness with high accuracy up to pressures of 3 MPa. Other recent studies with different atomizer geometries, pressures, and liquid properties have found that the expression estimates the liquid film thickness fairly well (Laurila et al, 2019;Wimmer & Brenn, 2013).…”
Section: Introductionmentioning
confidence: 69%
“…Convection terms are discretized with a Gamma-flux limited scheme ( Jasak et al, 1999 ) while linear schemes are used for all the other terms. We utilize the implicit LES approach as a stand-alone subgrid model similar to our previous studies ( Peltonen et al, 2018 , Peltonen et al, 2019 , Laurila et al, 2019 ).…”
Section: Models Methods and Softwarementioning
confidence: 99%
“…Recently, a geometric VOF method has also been implemented as a part of the isoAdvector [32] solver, which was used in present study. This solver reportedly offers a sharper interface tracking than the MULES [33,34].…”
Section: Methodsmentioning
confidence: 99%